Cognition, Semantics and Philosophy
XXI, 324 p.
Keywords: THE PLACE OF PHILOSOPHY IN COGNITIVE SCIENCE During the last few years, many books have been published and many meetings have been held on Cognitive Science. A cursory review of their contents shows such a diversity of topics and approaches that one might well infer that there are no genuine criteria for classifying a paper or a lecture as a contribution to Cognitive Science. It is as though the only criterion is to have appeared in a book or in the programme of a meeting or title we can find the expression " . . . Cognitive Science" in whose name or something like that. Perhaps this situation is due to the (relative) youth of the field, which is seeking its own identity, still involved in a process of formation and consolidation within the scientific community; but there are actually deep disagreements about how a science of the mind should be worked out, including how to understand its own subject, that is, "the mind. "While for some the term makes reference to a set of phenomena impossible to grasp by any scientific approach, for others "the mind" would be a sort of myth, and the mental terms await elimination by other more handy and empirically tractable terms.